НАСКОЛЬКО ОТКРЫТЫ ОТКРЫТЫЕ ДАННЫЕ? ИССЛЕДОВАНИЕ ДВУХ ИРЛАНДСКИХ ВЕБ-САЙТОВ С ОТКРЫТЫМИ ПРАВИТЕЛЬСТВЕННЫМИ ДАННЫМИ - Хайят, Машаэл; Абулола, Омар; Хайят, Манал (Вопросы государственного и муниципального управления, 2022)
In discussions of Open Government Data (hereafter referred to as open data or OGD) in the academic literature, the question of what is meant by the word "open"? has to date received only limited attention. The use of Open Government Data (OGD) has spread globally as governments make more of their data available via electronically accessible formats for individuals to use and share. OGD is seen as something that has the potential to play an important role in achieving transparency, and accountability, enabling new forms of civic participation, and stimulates economic growth and development. However, there is a need to examine OGD datasets to determine whether they are truly open. The purpose of this paper is to investigate OGD openness based on a number of existing or proposed open data definitions and principles. The principles proposed by the work of the Open Government Working Group will be analyzed. The methodology that has been used to collect the data includes OGD website content analysis, participant observation and semi-structured interviews using purposeful and snowball sampling techniques. The results in this paper are just part of the overall study. This research has not been funded. The research limitation is it has been done only in the Irish context. It is an original study with primary data. The conclusion of this research mainly demonstrates that OGD in the Irish context is progressing but requires further work to be open based on the principles proposed by the Open Government Working Group works.